A chromosome-scale genome assembly of Quercus gilva: Insights into the evolution of Quercus section Cyclobalanopsis (Fagaceae) - Zhou, Xia; Liu, Na; Jiang, Xiaolong; Qin, Zhikuang; Farooq, Taimoor Hassan; Cao, Fuliang; Li, He (Frontiers in Plant Science, 2022)
Quercus gilva is an ecologically and economically important species of Quercus section Cyclobalanopsis and is a dominant species in evergreen broad-leaved forests in subtropical regions of East Asia. In the present study, we reported a high-quality chromosome-scale genome assembly of Q. gilva, the first reference genome for section Cyclobalanopsis, using the combination of Illumina and PacBio sequencing with Hi-C technologies. The assembled genome size of Q. gilva was 889.71 Mb, with a contig number of 773 and a contig N50 of 28.32 Mb. Hi-C scaffolding anchored 859.07 Mb contigs (96.54% of the assembled genome) onto 12 pseudochromosomes, with a scaffold N50 of 70.35 Mb. A combination of de novo, homology-based, and transcript-based predictions predicted a final set of 36,442 protein-coding genes distributed on 12 pseudochromosomes, and 97.73% of them were functionally annotated. A total of 535.64 Mb (60.20%) of repetitive sequences were identified. Genome evolution analysis revealed that Q. gilva was most closely related to Q. suber and they diverged at 40.35 Ma, and Q. gilva did not experience species-specific whole-genome duplication in addition to the ancient gamma () whole-genome triplication event shared by core eudicot plants. Q. gilva underwent considerable gene family expansion and contraction, with 598 expanded and 6,509 contracted gene families detected. The first chromosome-scale genome of Q. gilva will promote its germplasm conservation and genetic improvement and provide essential resources for better studying the evolution of Quercus section Cyclobalanopsis.